INDIVIDUAL COUNSELING SYSTEMATIC DESENSITIZATION TECHNIQUES TO REDUCE PHOBIA TO CANDY - Ayu Wandira; Yeni Karneli (Literasi Nusantara, 2022)
This article discusses individual counseling of systematic desensitization techniques to reduce candy phobia. The client is a 23 year old woman who has a specific phobia of sweets. The methods used in this individual counseling are clinical interviews and observation. The results of clinical interviews at the first counseling meeting, the client was identified as having irrational thoughts about sweets. The client considers that candy is a dirty and disgusting object, the client also experiences excessive anxiety and fear when seeing, holding, touching the candy. The last time the client ate sweets was when he was 5 years old. This is due to the client's bad experience with candy. The client's parents strictly forbid the client not to eat sweets because the client often has problems with teeth, the client's parents scare the client about sweets which causes the client to develop bad thoughts about candy. Another thing that makes the client's fear and anxiety grow, the client's relatives often frighten the client and throw candy at the client, this makes the client (screaming, crying, holding his hands and running away from candy). The intervention given in this individual counseling was Systematic Desensitization which was carried out for 11 sessions. The purpose of this intervention is that the client is able to reduce anxiety and fear of candy and can respond naturally when seeing, holding, touching and eating candy. The results of the intervention the client was able to respond naturally when seeing, touching and holding candy, the client was also able to control anxiety and fear of candy.